Materi Budaya dalam Produksi Siaran Televisi - Surianor . (Alhadharah: Jurnal Ilmu Dakwah, 2013)
Television is still the dominant medium for most public spectacle. These conditions require the willingness of producers to present television program content of a higher quality and beneficial to the community. One of the important broadcast content to be presented to the community is a culture, because culture is a part of people's lives. Cultural content is currently in a challenge, because it is the less desirable and relatively minimal television broadcast content. Foreign cultures that are used as broadcast content may be againts the teachings of Indonesian religions and cultures. This needs the attention and responsibilities of all parties.  It required the ability to make cultural content  as  television program, to make it  interesting and to coloure them with religious teachings, and to broadcast positive cultural and educational impact for the community